Proses Islamisasi, Perkembangan, dan Eksistensi Islam di Perancis - Suparto Iribaram (TASAMUH: Jurnal Studi Islam, 2018)
This paper will describe the historical development of Islam in France, including its existence and problems as a minority. The process of Islamization has long been rising in France, because the French people themselves have long been in contact with Islam, precisely since Islam entered in the 8th century, for about 40 years in the southern part of France, namely the transition period of power from the Umayyad Dynasty to the Dynasty Abbāsiyah. Furthermore, though hampered by the Crusades and expansion, the Islamization process in France explicitly began in 1830, when Muslim immigrants came to bring their commodity to France, when the era of North African colonization began. Since that time the population of Muslims in France experienced significant developments. The number of Muslims in France in 2005 has reached 5,000,000 people and there are about 2,500 mosques; the majority of them are from North Africa Sunni. However, the problems faced by French Muslims today are the marginalization of such regulations as the ban on jilbab (hijab), the existence of negative prejudices and fear of terrorism and radicalism